QUALITY FUNTION DEPLOYMENT METHOD FOR ASCERTAINING INFLUENTIAL FACTORS ON TRANSFER OF SAFETY TRAINING SKILLS IN INDIAN CONSTRUCTION ORGANIZATIONS - Prasad, Raja; P, Venkata Chalapathi (Journal of Technical Education and Training, 2016)
Safety training is crucial activity of an injury and illness prevention program that can assist management to identify and mitigate workplace hazards. Effective safety training will contribute towards transforming employees competent in health and safety aspects, to minimize accidents and eliminate the costs of accidents. Translating knowledge gained of safety training into the workplace environment by employees will assist the organizations to minimize work-related injuries. Most of the construction organizations in India are imparting safety trainings to all levels of employees and its impact on work place safety is marginal. In order to better understand factors influencing the transfer of safety knowledge acquired during trainings in construction organizations, quality function deployment technique has been applied; the trainee’s expectations and technical requirements were analyzed. The study proposes to identify factors and to assist managements of Indian construction organizations to understand the interaction among trainee’s expectations and technical requirements. Support from superiors, perceived importance and self-efficacy the most important expectation of trainees. Organization culture, management commitment and working environment are the most important technical requirements for better transfer of safety training skills.